2010
DOI: 10.2337/db09-0745
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Insulin Resistance After Insulin-Induced Hypoglycemia in Humans: The Role of Lipolysis

Abstract: OBJECTIVEChanges in glucose metabolism occurring during counterregulation are, in part, mediated by increased plasma free fatty acids (FFAs), as a result of hypoglycemia-activated lipolysis. However, it is not known whether FFA plays a role in the development of posthypoglycemic insulin resistance as well.RESEARCH DESIGN AND METHODSWe conducted a series of studies in eight healthy volunteers using acipimox, an inhibitor of lipolysis. Insulin action was measured during a 2-h hyperinsulinemic-euglycemic clamp (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 51 publications
5
43
0
1
Order By: Relevance
“…An escape of ketogenesis from inhibition by insulin during hypoglycaemia has been shown in pancreatectomised dogs undergoing a hyperinsulinaemic clamp with euglycaemia or hypoglycaemia (10). Moreover, similar results were observed during hyperinsulinaemic hypoglycaemia in humans (11). Lipolysis can escape the inhibitory effect of insulin during the rise in counter-regulatory hormone levels.…”
Section: Discussionsupporting
confidence: 53%
“…An escape of ketogenesis from inhibition by insulin during hypoglycaemia has been shown in pancreatectomised dogs undergoing a hyperinsulinaemic clamp with euglycaemia or hypoglycaemia (10). Moreover, similar results were observed during hyperinsulinaemic hypoglycaemia in humans (11). Lipolysis can escape the inhibitory effect of insulin during the rise in counter-regulatory hormone levels.…”
Section: Discussionsupporting
confidence: 53%
“…Recent research supports the notion that obese individuals have a higher baseline lipolytic rate and an increased release of NEFA during starvation than lean individuals [19] . Further, studies on insulin-induced hypoglycemia reinforce the concept that NEFA levels decrease initially, reaching a nadir at 30 min that lasts about 90 min, and then increase parallel to enhanced catecholamine release [20][21][22][23][24] . It appears that blood glucose levels that elicit counter-regulatory hormone release are slightly higher in obese than lean persons.…”
Section: Hypoglycemia Promotes Nefa Elevationsmentioning
confidence: 72%
“…However, research on humans has provided information about the effects of sequential in vivo exposure of muscle to elevated circulating insulin concentration on glucose metabolism. Studying humans undergoing two sequential euglycemic hyperinsulinemic clamps that were 15 h apart, Lucidi et al (73) found no enhancement of glucose disposal during the second clamp compared with the first clamp. Jovanovic et al (60) studied the second-meal phenomenon, which refers to the well-documented observation that postmeal glycemia is lower after the second of two similar meals that are spaced several hours apart.…”
Section: Potential Triggersmentioning
confidence: 99%
“…The greater glycogen accumulation after the breakfast-plus-lunch trial vs. the lunch-only trial was characterized by similar insulinemia, lower glycemia, and lower nonesterified fatty acids. The results of these studies using nonexercised rats or humans are interesting (41,60,73), but it is unclear whether these experiments are truly relevant to the postexercise increase in insulin sensitivity.…”
Section: Potential Triggersmentioning
confidence: 99%